Indonesia's International Political Strategy in Anticipating the Negative Impacts of War - Indra Satria (International Journal of Law Society Services, 2025)
The current escalation of global armed conflict has triggered supply chain shocks and energy inflation that threaten national stability. This study aims to analyze Indonesia's foreign policy strategy in mitigating these systemic impacts through the Free and Active principle. Using a descriptive qualitative method based on literature studies, data were collected from official documents, national regulations, and international legal instruments. The results show that Indonesia has successfully carried out its role as a bridge builder through pragmatic diplomacy and the utilization of legal frameworks such as UNCLOS 1982. The conclusion of the study confirms that consistency in the Free and Active policy effectively protects economic sovereignty and strengthens Indonesia's bargaining position as a world peace mediator amidst the polarization of major powers.